Factors affecting ecological footprint in Saudi Arabia: a panel data analysis - Aldegheishem, Abdulaziz (Frontiers in Environmental Science, 2024)
The global environment has witnessed an increase in environmental risks over the last few decades due to the rising demand for energy to support economic development and urbanization. These environmental risks are exacerbated by the escalating human activity that depletes natural resources. Therefore, analyzing factors affecting Ecological Footprint (EFP), which include many variables such as urbanization, energy consumption, natural resources, economic growth, and technological innovation, is essential to achieve sustainable development. Urbanization is a key driver of economic growth. Achieving economic development requires the utilization of natural resources and energy which increase the EFP. Therefore, the focus on technological innovation is essential to reduce the EFP. Despite the critical environmental and economic implications of factors affecting EFP, studies on this area are lacking, especially across Middle Eastern countries, and present contradictory findings. Therefore, the main aim of this study is to investigate the effect of urbanization, energy consumption, natural resources, economic growth, and technological innovation on the EFP in Saudi Arabia. To this end, the study utilizes an autoregressive distributed lag (ARDL) model, which is considered the most suitable econometric approach when variables are stationary at I(0) or integrated of order I(1), based on data collected from various international sources for the period spanning from 1990 to 2022. In both the long run and the short run, empirical findings show that urbanization, natural resources, and technological innovation decrease the EFP, while energy consumption and economic growth increase the EFP. These results reveal that energy policies need to be addressed, and economic growth is unable to lower the EFP due to a lack of connection between economic policies and environmental goals. On the other hand, the study shows that urban policies and the management of natural resources are effectively linked to environmental goals. These findings have several significant policy implications for reducing the EFP. Suggestions include effectively linking economic policies to environmental goals by electrifying the economy. Additionally, several procedures should be considered, including replacing current carbon-based energy with renewable sources, reevaluating the pricing of the energy system, increasing taxes on carbon-based energy, and reassessing current energy laws and regulations.